Tuberculosis risk in patients with rheumatoid arthritis - Gamboa, Rocío (2006)
Background: Studies on tuberculosis (TB) risk in patients with rheumatoid arthritis (RA) non-users of biological therapy show contradictory results. Objetives: To determine RA as independent risk factor for TB. Design: Non concurrent cohort study. Setting: Guillermo Almenara Asistential Net, Lima-Peru, a teaching hospital. Participants: Biological therapy non-users RA patients. Interventions: RA patients fulfilled the ARA 1987 diagnosis criteria and were biological therapy non-users. Control group was paired by age and sex to RA patients. Patients in control groups had non immunological disorders. Clinical information was completed by interviews. RA patients follow-up was started at the time of diagnosis and ended at the time of interview and/or TB diagnosis. Density incidence (DI) was found for each cohort and TB relative risk (RR) was calculated. To evaluate time length to TB evolution a Kaplan Meier curve was graphed and compared both groups with log-rank test. Drugs and predisposing TB pathologies were analyzed. Main outcome measures: Tuberculosis in patients with rheumatoid arthritis. Results: Six hundred and seventy six out of 808 RA patients and 664 controls qualified for inclusion criteria’s. RA and control groups reached 6 940,75 and 6 666,53 follow-up patients-year, respectively. RA cohort mean age was 46,65 at RA diagnosis. Only 29,7% of RA patients had a positive tuberculin reaction. Fifteen TB cases were identified in the RA cohort and 8 at the control group, yielding a mean DI of 216,1/100 000 and 122,1/ 100 000 patients-year respectively. TB RR was 1,8 (IC 95%=0,8- 4,2), and after adjusting drugs and co-morbidity the HR was 1,69 (IC 95%=0,26-10,93). Statistically significant difference was not found with Kaplan Meier curves comparison (p=0,19). Conclusions: We did not find a higher risk of rheumatoid arthritis patients to develop tuberculosis.